Deconstruction / interpretation and the crisis of digital literature in the work of Aïn Abdelghani Bara - chaki, zahira (El Omda in Linguistics and Discourse Analysis, 2025)
The research aims to reveal the critical role of Abdelghani Bara .some of his contributions to contemporary Aral criticisme bases on revealing his interpretive vision ; which represented his critical distinction including what related to digital literature .moreover ;the concept of digital literature after its dismantling appears to be a concept plagued by many difficulies and crises in reception hermeneutic ;intruction , and the problem of identity.